Anterior Segment Tomography with the Cirrus Optical Coherence Tomography - Eduardo B. Rodrigues; Margara Johanson; Fernando M. Penha (Journal of Ophthalmology)
Optical coherence tomography (OCT) is an optical acquisition method to examine biological tissues. In recent years, OCT has become an important imaging technology used in diagnosing and following macular pathologies. Further development enabled application of optical coherence tomography in evaluation of the integrity of the nerve fiber layer, optic nerve cupping, anterior chamber angle, or corneal topography. In this manuscript we overview the use of OCT in the clinical practice to enable corneal, iris, ciliary body, and angle evaluation and diagnostics.